2020
DOI: 10.1038/s41598-020-59240-8
|View full text |Cite
|
Sign up to set email alerts
|

Organosilicons of different molecular size and chemical structure as consolidants for waterlogged archaeological wood – a new reversible and retreatable method

Abstract: Ineffectiveness of the chemicals applied so far for waterlogged wood conservation created the need to develop new more, efficient and reliable agents. As an alternative, a new method with the use of organosilicon compounds differing in chemical composition and molecular weight has been investigated. The results obtained show the potential of organosilicons as consolidants in waterlogged wood conservation able to effectively stabilise wood dimensions upon drying. The best wood stabilisers were low-molecular org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 43 publications
1
46
0
Order By: Relevance
“…The samples of wood treated with silane 2 (A2) present most informative bands at 1340 (8) and 1308 (8) cm −1 assigned to deformation of -CH 2 groups present in the spectra due to existence of a larger number of these groups in the solid network. Furthermore, similarly to A1, were observed bands at 1187 (10), 1130 (11), 1030 (14), 1004 (14), 918 (16), 861 (17), 807 (19), 768 (20), 692 (21), and 474 (22) cm −1 (see assignments in Table 1).…”
Section: (A) (B)supporting
confidence: 52%
See 2 more Smart Citations
“…The samples of wood treated with silane 2 (A2) present most informative bands at 1340 (8) and 1308 (8) cm −1 assigned to deformation of -CH 2 groups present in the spectra due to existence of a larger number of these groups in the solid network. Furthermore, similarly to A1, were observed bands at 1187 (10), 1130 (11), 1030 (14), 1004 (14), 918 (16), 861 (17), 807 (19), 768 (20), 692 (21), and 474 (22) cm −1 (see assignments in Table 1).…”
Section: (A) (B)supporting
confidence: 52%
“…The results of the research by Broda et al [21,22] clearly showed that the stabilisation effect on waterlogged wood depends mainly on the type of an organic group attached to a silicon atom in organosilicons. Great dimensional stabilisation of waterlogged wood was obtained among other things due to methyltrimethoxysilane (MTMS), (3-mercaptopropyl) trimethoxysilane (MPTES) and 1,3-bis(diethylamino)-3-propoxypropanol)-1,1,3,3tetramethyldisiloxane (DEAPTMDS) treatment, reaching anti-shrink efficiency values of about 81%, 98% and 90%, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…), excavated from debris of the mediaeval "Poznań" bridge at the bottom of the Lednica Lake (the Wielkopolska Region, Poland), was used for the study. The elm log consisted only of heartwood, and although apparently well-preserved in appearance, it proved to be severely degraded, with the loss of wood substance (LWS) estimated at 70-80% and significantly reduced hemicelluloses and cellulose content (Broda et al 2020;Spear and Broda 2020).…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 5 Consequently, the main concern related to the drying process is the loss of the original structure and, therefore, the loss of the historical artwork itself. 6 New protocols have been developed for the conservation of cultural heritage. 7 , 8 Colloidal engineering has become a deeply investigated research domain, and many synthetic routes have been proposed for chemists and materials scientists.…”
Section: Introductionmentioning
confidence: 99%